Vulnerability, justice and care - Annalisa Verza (Oñati Socio-Legal Series)
The concept of vulnerability is once again assuming a central role in ethical-political-legal discourse. This is the case both in relation to its neo-liberal reinterpretations, aimed at placing the responsibilities and consequences of vulnerability onto the vulnerable subject itself, and, on the contrary, to the theses - the result, to a large extent, of a reworking of the ethics of care – of authors such as Martha Fineman, Judith Butler, Martha Nussbaum, Catriona Mackenzie and others, who use the idea of vulnerability as a basis for re-founding and reorganising liberal policies, freeing them from fictitious concepts such as the alleged basic autonomy of the human being. The article aims to analyse the different meanings and implications that, due to the accentuation of different aspects of vulnerability, add up to produce such a multifaceted concept, in order to try to clarify the conceptual implications and practical consequences that vulnerability may elicit.